Planificación estratégica y su incidencia en los resultados del Patronato Municipal de Amparo Social del G.A.D Latacunga - Segovia Benítez, Juan Xavier (2023)
Strategic planning raises horizons that must be worked on in the long, medium and short term; the Board of Trustees has not generated a planning system that allows it to set a long-term horizon; it has limited itself to working with annual operating plans that reflect a short-term vision; What further aggravates the problem is that the plans are managed under traditional measurement systems, focusing only on historical economic indicators; That is the problem that originates the present investigation. The work was based on a qualitative, non-experimental and correlational approach, based on the planning and results variables. The current situation of the board of trustees was diagnosed using the Balanced Scoredcard (BSC) methodology or comprehensive scorecard for process management and it was determined following the adapted methodology of Sierra (2022) that the institution suffers from a managerial attention disorder.